Probiotic-Based Therapy for Active Tuberculosis Infection: The Role of Gut-Lung Axis and Granulocyte Macrophage-Colony Stimulating Factor - Made Indira Dianti Sanjiwani; Nyoman Budhi Wirananda Setiawan; Agus Indra Yudhistira Diva Putra; Agus Eka Darwinata (Faculty of Medicine Universitas Airlangga, 2021)
Tuberculosis is a global health problem with a total of 1.4 million cases in 2015. Over the last decade, several studies have demonstrated the potential role of gut-lung axis in the treatment of tuberculosis. The exact mechanism of the gut-lung axis on tuberculosis is still unknown, however modulation of the gut-lung axis can be performed via probiotic administration. The administered probiotics are capable of inducing an immunomodulating effect which helps in the process of tuberculosis infection. One of the molecules that can be activated with probiotics and plays a role in tuberculosis infection is granulocyte macrophage-colony stimulating factor (GM-CSF). GM-CSF can control intracellular production of M. tuberculosis, inflammation in granulomas, and lung tissue reparation. This article aimed to explore the role of the gut-lung axis, GM-CSF, and the potential of probiotic-based therapy on active tuberculosis infection. It was found that probiotics mediate the immune response via the activation of several inflammatory cytokines and interleukins related to lung infection, but not directly with the tuberculosis pathogen. Thus, probiotic-based therapy has the potential to increase immunity during active tuberculosis infection. Further studies to explore the other mechanisms of the gut-lung axis against tuberculosis through probiotic administration need to be performed.